Pertimbangan Hakim Dalam Menggunakan Alat Bukti Pemeriksaan Di Tempat Dan Kekuatan Pembuktiannya Dalam Pemeriksaan Sengketa Waris Di Pengadilan Agama Karanganyar (Studi Putusan Nomor : 0516/Pdt.G/2011/PA.Kra) - Putut Eko Cahyono (Sebelas Maret University, 2013)
The aims of this research is to know the judge consederation on verdict case number : 0516/Pdt.G/2011/PA.Kra at Karanganyar relegion court. This is an empirical law research which is descriptif research. The kind of data used are primary and secondary data. This research reveals that Knowing situation of the land is the aim of using of checked unmovable things (i.e land) and the witness as evidences. Key words : legacy case, the power of evidence, on location checked, judge consideration.